2012
DOI: 10.1002/anie.201205426
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression and Manipulation of Three Tetracycline Biosynthetic Pathways

Abstract: Three and one: Three tetracycline biosynthetic pathways have been overexpressed and manipulated in heterologous host Streptomyces lividans K4-114. New tetracycline modifying enzymes have been identified through a series of gene inactivation and intermediate characterization. The collection of newly discovered tailoring enzyme and the heterologous platform will promote our understanding of tetracycline biosynthesis, as well as our performance to engineer tetracycline biosynthesis in an efficient manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 34 publications
(48 reference statements)
0
41
0
Order By: Relevance
“…This enzyme can also perform the equivalent reaction for tetracycline. Closely related enzymes are involved in the same step during biosynthesis of chlorotetracycline (CtcR) and dactylocyclinone (DaCO4) in Streptomyces aureofaciens and Streptomyces rimosus (29,386). Encoded by the oxytetracycline (oxy), chlorotetracycline (ctc), and dactylocyclinone (dac) gene clusters (29), these enzymes are members of the flavin/deazaflavin oxidoreductase (FDOR) superfamily (30) and utilize F 420 H 2 reduced through the action of Fno (387).…”
Section: Streptomycetesmentioning
confidence: 99%
“…This enzyme can also perform the equivalent reaction for tetracycline. Closely related enzymes are involved in the same step during biosynthesis of chlorotetracycline (CtcR) and dactylocyclinone (DaCO4) in Streptomyces aureofaciens and Streptomyces rimosus (29,386). Encoded by the oxytetracycline (oxy), chlorotetracycline (ctc), and dactylocyclinone (dac) gene clusters (29), these enzymes are members of the flavin/deazaflavin oxidoreductase (FDOR) superfamily (30) and utilize F 420 H 2 reduced through the action of Fno (387).…”
Section: Streptomycetesmentioning
confidence: 99%
“…However, during th e last decade, the most signifi cant insight into OTC biosynthesis has been gained by Tang´s research group at the University of California, Los Angeles (USA) (57)(58)(59)(60)(61)(62)(63).…”
Section: Biosynthetic Pathway Of Tetracycline Antibioticsmentioning
confidence: 99%
“…Based on amino acid sequence analyses, OtcR and Ctc11 (CtcB) from S. aureofaciens share 46 % identity; furthermore, the predicted SARP-binding sites were also identifi ed in the ctc cluster. Interestingly, Wang et al (62) found that the SARP regulator, encoded by ctc11 (ctcB) from the CTC gene cluster (ctc) of S. aureofaciens (36), could activate the transcription of the oxy cluster in the heterologous host Streptomyces coelicolor (62). Since OTC and CTC are structurally highly similar antibiotics, it is reasonable to expect similar biosynthetic and regulatory mechanisms.…”
Section: Regulation Of Tetracycline Biosynthesis and Genes Involved Imentioning
confidence: 99%
See 2 more Smart Citations